Analisis Pengaruh Modal, Volume Penjualan, dan Harga terhadap Pendapatan Pengecer Jeruk di Kota Pematang Siantar - Pawer Darasa Panjaitan; Dian G Purba; Nanang Nainggolan (Jurnal Ekuilnomi, 2024)
The aim of this research is to analyze the influence of capital, sales volume, and price on the income of orange retailers in Pematang Siantar City. The research period starts from January 2023-April 2023. The type of research used is a quantitative method with multiple linear analysis techniques. The research data is primary data and secondary data collected through questionnaires, interviews, and observations of 30 orange retailers in Pematang Siantar City. The results of the research show that the Fcount value is 17.777 > ftable 8.626 with a significance value of 0.000 < 0.05, which means that capital, sales volume, and price have a simultaneous influence on the income of orange retailers in Pematang Siantar City.